Woman and occupational health : issues and policy paper prepared for the global commission on women's health (Carouge, 1999)
"This excellent policy paper prepared for the Global Commission on Womens Health is an important resource for trade unionists and all those interested in improving working conditions for women and men. It provides comprehensive and reliable information on the workplace hazards experienced by women in all sectors. A number of authors provide papers, including Understanding Occupational Disease in Women Workers, Migration, Workforce and Health, Reproductive Health and Occupational Hazards among Women Workers. "